Potential of Parijoto (Medinilla speciosa) Fruits and Leaves in Male Fertility - Wijayanti, Dwi; Ardigurnita, Firgian (ANIMAL PRODUCTION, 2018)
The purpose of the study was to find out the potential of parijoto fruit and leaves qualitatively and quantitatively in male fertility. The content of fruits and parijoto were secondary compounds in the form of flavonoids, saponins, tannins, terpenoids, beta-carotene and antioxidants. Fertility is also needed in male animals. Decreased fertility in male cause a decrease in livestock productivity results in a decrease in gain from farmers. Handling of animals that occur after fertilization was usually carried out by injecting prostaglandin hormones. However, the relatively expensive price of hormones causes many farmers not to be able to buy. Another alternative that could cause a decrease in fertility was to use herbal plants, namely parijoto. The use of Parijoto plants was not certain which relevanted in fertility. Need to be tested first about phytochemical screening on parijoto leaves and fruit. The results of parijoto leaf and fruit analysis were qualitative and quantitative. The content of fruits and parijoto were secondary compounds in the form of flavonoids, saponins, tannins, terpenoids, beta-carotene and antioxidants. Parijoto fruits were founded flavonoids and saponins namely 3. 61% b/b and 3. 71% b/b. Total flavonoids and saponins in Parijoto leaves were 2.65% b/b and 4.19% b/b. Total antioxidants, total polyphenols, tannins in parijoto leaves and fruit respectively were 36.84 ppm; 3.95%; 3.52% and 20.06 ppm; 12.68%; 11.70%. The conclusion was that part of the parijoto fruit and leaf were the potential in male fertility.Â Key words:Â  Antioxidants, Fertility, Flavonoids, Males, Parijoto.